Not a box of nuts and bolts: Distribution channels for specialty drugs? - XU, Liang (Institutional Knowledge at Singapore Management University, 2023)
One of the most important trends in the pharmaceutical industry is the rapid growth of specialty drugs. Specialty drugs, mostly bio based, tend to be high risk, high priced, and more regulated than traditional drugs, resulting in unprecedented challenges in distribution. Such challenges lead to the emergence of specialty distributors (SDs), which, compared with traditional wholesalers (WSs), represent a more controlled channel and carry a smaller variety of drugs. Due to the risky nature of specialty drugs, manufacturers must consider the trade-off between access and control in determining whether to use SDs (partially or exclusively). Using a unique dataset assembled from multiple proprietary and public data sources on the transactions for 419 specialty drugs across 11 manufacturers (including 8 of the top 15 manufacturers), 161 distributors, and 129,911 points of care (POCs) in 2012–2015, we investigate how the competing factors of access and control influence manufacturers’ usage of SDs (vs. WSs), with access indicated by downstream POCs’ required product variety and control indicated by regulations on the network. We find that interestingly, the imposition of the regulations in general on the product is not associated with higher usage of SDs, but the imposition of the regulations with a specific element (restrictive access) is. In addition, downstream POCs’ need for convenient access to the required drug variety is associated with lower SD usage. Our study contributes to the limited supply chain literature on risky products and the limited empirical research on Business-to-Business (B2B) distribution decisions, and provides important insights and guidance to manufacturers, downstream POCs, and regulators.